EDUKASI ECO ENZYME DARI LIMBAH BUAH DAN SAYUR MENJADI SABUN CAIR CUCI TANGAN SEBAGAI UPAYA MENCIPTAKAN EKONOMI MASYARAKAT PRODUKTIF DALAM MENDUKUNG SUSTAINABLE DEVELOPMENT GOALS (SDGs) DI KELURAHAN KETINTANG 4 SURABAYA - Umarudin, Umarudin; Syukrianto, Syukrianto; Anidnya, Widya Dara; Wulansari, Silvi Ayu; Aryanti, Evy (Universitas Mataram, 2024)
The abundance of fruit and vegetable waste in the Ketintang 4 area has a detrimental impact on the surrounding environment. Therefore, it is necessary to implement educational initiatives on utilizing this waste to produce eco-enzyme, which can be used as an active ingredient in liquid hand soap. This activity aims to educate on eco enzymes from fruit and vegetable waste into liquid hand soap as an effort for Clean and Healthy Living Behavior (PHBS) and the